Pengembangan Website E-Commerce untuk Ekspansi Pasar Produk UMKM Menggunakan Model Prototipe - Rian Hilmi Hidayatullah; Kholid Haryono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The advancement of digital technology provides opportunities for Micro, Small, and Medium Enterprises (MSMEs) to develop marketing strategies through the utilization of electronic commerce platforms. However, the Baraya UMKM Community in Pangandaran, West Java, still experiences obstacles in market expansion due to marketing and sales methods that are still conducted conventionally. This research aims to design an e-commerce website that can facilitate digital marketing and transaction activities for the Baraya UMKM Community while assessing its functionality and ease of operation. The research approach adopts the Prototype method, which facilitates iterative system development by incorporating user feedback. This study involves the participation of 24 respondents comprising community administrators and MSME administrators as primary users of the platform. System verification is conducted through Black Box Testing to validate the conformity of all functions with requirement specifications, as well as usability evaluation using the System Usability Scale (SUS) instrument to analyze the system's practicality level. The usability evaluation results show an average SUS score of 74.58 with a Grade B category, indicating that the platform has an adequate level of practicality and is acceptable to users. Therefore, the developed e-commerce website is declared to meet the feasibility criteria as a medium for digital marketing and transactions in supporting the market expansion of MSME products within the Baraya UMKM Community environment.